2008
DOI: 10.1177/002070200806300106
|View full text |Cite
|
Sign up to set email alerts
|

Transnationalism, Active Citizenship, and Belonging in Canada

Abstract: He would like to thank the SSHRC's multiculturalism issues in Canada program's funding support for this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In contrast, Ramakrishnan (2005: 93–94) found that dual nationality increases the likelihood of voting among immigrants (except for Cubans) in the United States. Evidence from Canada also revealed that dual citizenship does not diminish civic participation and the sense of belonging to Canada (Wong, 2008: 87). While dual citizens seem to engage less in political participation, the author points to significant differences between ethnic groups in this respect.…”
Section: Dual Citizenship and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Ramakrishnan (2005: 93–94) found that dual nationality increases the likelihood of voting among immigrants (except for Cubans) in the United States. Evidence from Canada also revealed that dual citizenship does not diminish civic participation and the sense of belonging to Canada (Wong, 2008: 87). While dual citizens seem to engage less in political participation, the author points to significant differences between ethnic groups in this respect.…”
Section: Dual Citizenship and Its Consequencesmentioning
confidence: 99%
“…However, fears and hopes about dual citizens are often built on speculation. The rare empirical studies on this specific group are inconclusive and often struggle with insufficient data (Cain and Doherty, 2006; Staton et al , 2007a; Wong, 2008; Mügge, 2012). Based on comparative data on dual citizens in Switzerland, we want to make an empirical contribution to the question whether dual citizenship endangers the political integration of dual citizens and their loyalty to the residence country.…”
Section: Introductionmentioning
confidence: 99%
“…Also it is often argued that involvement with the country of origin hinders engagement in the host society. This popular belief is not supported by academic research; ties with the country of origin can be combined with involvement in the host country (Carling, 2008;Marcelli and Lowell, 2005;Portes et al 2002;Snel et al 2006;Wong, 2007).…”
Section: Transnationalism: a Theoretical Framework In Comparative Permentioning
confidence: 99%
“…If not as a synonym of identity, belonging is used as a synonym of or in association with the notion of citizenship, once again in a more or less explicit way and without any attempt to define in which sense belonging might be different from citizenship (and identity). Examples of this usage equally abound among geographers (Ho 2006, 2009; White and Gilmartin 2008; Winders 2007), sociologists (Clark 2009; McNevin 2006; Wong 2007), anthropologists (Getrich 2008; Rosaldo 1994), political scientists (Clark 2009; Hampshire 2005; Mason 2000; Varsanyi 2005), jurists (Bhabha 1999; Kaplan 1993), and also historians (Fahrmeir and Jones 2008). In other cases again, belonging is evoked in association with both (national) identity and citizenship, without any attempt, once more, to discuss its theoretical or analytical specifics.…”
Section: Introductionmentioning
confidence: 99%